Current diagnosis & treatment pediatric - Hay, William W. (McGraw-Hill Medical, 2012)
Suitable for pediatricians, family practitioners, physician assistants, nurses and nurse practitioners, and the critical care unit, this title focuses on the care of children from birth through adolescence. It emphasizes the clinical aspects of pediatric care while also covering important underlying principles.